Biomechanics of the paretic knee during overground gait in people with stroke: a systematic review. (25th November 2022) - Waller, Clifford Paul; Sangelaji, Bahram; Hargest, Claire; Woodley, Stephanie J.; Lamb, Peter; Kuys, Suzanne; Calder, Allyson; Hale, Leigh A.
Abstract: Background: Biomechanics of the paretic knee during gait are well documented, yet these data have yet to be systematically summarised and analysed. Objective: To analyse three-dimensional optic-based biomechanical data of the paretic knee post-stroke, compared to non-paretic or control participants' knees, during overground gait. Methods: Database searches were completed, with observational studies and baseline data from randomised controlled trials considered. Two reviewers independently screened studies, extracted data, and determined risk of bias using the Downs and Black Quality Index. Quantitative and descriptive analyses were undertaken, with level of evidence considered. Results: 31 studies were included, with 719 participants with stroke and 274 controls. Pooled data were heterogenous. Descriptive analyses demonstrated: reduced peak knee flexion at the paretic knee compared to non-paretic knee; reduced knee flexion during swing at the paretic knee compared to control knee; reduced sagittal range of motion at the paretic knee compared to non-paretic, and control knee; and reduced peak (internal) extension moments at the paretic knee compared to non-paretic knee. Most studies were at high risk of bias, demonstrating limited quality evidence in the current evidence base. Conclusion: The paretic knee demonstrated reduced peak knee flexion, knee flexion during swing, range of motion, and knee extension moments compared to the non-paretic and/or control knee. Considerable heterogeneity prevented meta-analyses. The current evidence base reflects limited quality, with further research required to better explore biomechanical differences occurring in well documented post-stroke gait patterns.